Dental Image Analysis for Disease Diagnosis - Jain, Kavindra R.; Chauhan, N. C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides an overview of computational approaches to medical image examination and analysis in oral radiology utilizing dental radiograph to detect and diagnose dental caries in cases of decayed teeth. Coverage includes basic image processing techniques; approaches for Region of Interest extraction and analysis; and the role of computational clustering techniques for segmentation of teeth and dental caries. The book also presents a novel multiphase level set method for automatic segmentation of dental radiographs.
Introduction -- Domain Study and Literature Review -- Enhancement and Segmentation of Dental Radiographs Using Morphological Operations -- Segmentation of Dental Radiographs Using Active Contour Model -- Multiphase Level Set Segmentation for Roi Extraction from Dental Radiographs -- Clustering Techniques for Dental Image Analysis -- Conclusion and Further Enhancements.
Keywords: Biomedical engineering; Dentistry; Signal processing; Radiology; Computer vision; Biomedical Engineering and Bioengineering; Dentistry; Signal, Speech and Image Processing; Radiology; Computer Vision